The autism advantage at work: A critical and systematic review of current evidence - Bury, Simon M.; Hedley, Darren; Uljarević, Mirko; Gal, Eynat (Research in developmental disabilities, 2020)
•Individuals with autism are marketed as bringing an autism advantage to employment.•Experimental research and clinical opinion support the potential for unique strengths.•Insufficient ecological evidence in the workplace supporting an autism advantage.•An individual differences approach to autism strengths in employment is argued. Despite difficulties entering the workforce, people on the autism spectrum are often successful. Furthermore, they are suggested to bring unique abilities (e.g., attention to detail, tolerance for repetitive tasks) related to the repetitive and restrictive behaviours and interests (RRBI) diagnostic domain, that may be advantageous in employment. This critical and systematic review examined evidence supporting the superior workplace performance of employees on the autism spectrum, particularly regarding the RRBI domain. A systematic review (PRISMA guidelines) evaluated empirical peer-reviewed studies that assess employees on the autism spectrum’s performance in the workplace or on work-specific tasks. Nine databases were searched, with additional papers identified from reference lists and consultation. Two quantitative and four qualitative papers met criteria. Results reflect themes; attention to detail, tolerance of repetitive tasks, special/circumscribed interests, other RRBI related advantages/concerns. Due to the nature and quality of the identified studies there is currently no strong evidence supporting or negating a workplace autism advantage. This review highlights the need for more research and urges constraint in utilising stereotypes that may not apply to all on the autism spectrum, arguing an individual differences approach to supporting autism strengths at work.